Effort and Prospective on Nuclear Security in ROK - Jung Soo Kim; Myung-Tak Jung; Kookheui Kwon; YoungWook Lee (International Journal of Nuclear Security, 2022)
As of July 2013, the Republic of Korea (ROK) has been operating a total of 23 nuclear power reactors at four sites with five new reactors under construction. In addition, the country has planned to construct two more units at two candidate sites, but due to a change in the energy policy, only one candidate site has been constructed while the other was decommissioned. The ROK has also been exporting nuclear power plants to the United Arab Emirates (UAE) and building a research reactor in Jordan. These actions have made the nation’s nuclear industry by far the fastest growing industry in the world. While Korea has focused on improvements in the field of nuclear safety (especially after the Fukushima accident), it continues to strengthen nuclear security as well. This was demonstrated both when the country hosted the 2012 Nuclear Security Summit and when the nation’s president made a speech emphasizing the need for nuclear and cyber security during the 2014 Nuclear Security Summit (NSS). This paper examines the approaches leading to the establishment of the physical protection systems and their application at nuclear facilities in the ROK based on the Convention on the Physical Protection and Nuclear Materials (CPPNM). The paper also recommends further steps to improve the ROK’s existing nuclear security apparatus.
Keywords: Nuclear Security; Cyber Security; Nuclear Security Summit (NSS); Physical Protection